Pencitraan Kekerasan Saddam Hussein Terhadap Perempuan Sebagai Propaganda Amerika Serikat - Machya Astuti Dewi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2004)
Through internet, the United States has been shaping public opinion by the way of presenting Saddam Hussein as regime who commits a violent against women. This case indicated that gender issue gains more significance in international politics.